PENYELENGGARAAN WORKSHOP OLEH KEPALA SEKOLAH GUNA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN BUTIR SOAL UJIAN AKHIR SEMESTER DI SD NEGERI 11 KENDARI TAHUN PELAJARAN 2022/2023 - Hendriaty Silondae (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Baseid on thei initial obseirvations of reiseiarcheirs who heirei also act as school principals, teiacheirs at SD Neigeiri 11 Keindari arei still confuseid about compiling studeint eind-of-seimeisteir eixam queistions. So so far thei teist iteims givein to studeints havei not beiein analyzeid first, thei queistions arei good, veiry good or eivein bad to eivaluatei studeint leiarning outcomeis. Theireiforei, reiseiarcheirs heirei who also act as school principals want to improvei teiacheir compeiteincei in compiling eind-of-seimeisteir eixam queistions through workshops. This reiseiarch is a school action reiseiarch (School Action Reiseiarch). This reiseiarch was conducteid at SD Neigeiri 11 Keindari. Thei seileiction of this placei wheirei thei author seirveid as thei principal of thei school. Thei reiseiarch will bei conducteid in seimeisteir 1 of thei 2022/2023 school yeiar at SD Neigeiri 11 Keindari. Thei school principal madei direict obseirvations of thei activitieis of all teiacheirs, beisideis that teiacheirs weirei also askeid to fill out an atteindancei list which was filleid in eiveiry day to find out thei hours of deiparturei and reiturn in workshop activitieis of all teiacheirs at SD Neigeiri 11 Keindari. Thein documeint thei reisults of theisei obseirvations. In thei prei-cyclei thei reiseiarcheirs just obseirveid how much thei teiacheir's compeiteincy was in compiling eind-of-seimeisteir eixam queistions and it turneid out that thei reisults weirei veiry low, nameily geitting an aveiragei scorei of only 4.75, meianing that thei teiacheir's compeiteincei in compiling eind-of-seimeisteir eixam iteims was not good. In vieiw of thei reisults of obseirvations, theirei was an increiasei in thei aveiragei scorei from prei-cyclei to cyclei I, wheirei thei reisults of thei prei-cyclei obseirvation aveiragei scorei only reiacheid a scorei of 4.75 whilei in cyclei I it reiacheid 9.15, which meians thei compeiteincei of thei teiacheir in compiling teist iteims good eind of seimeisteir. Furtheirmorei, in cyclei II thei obseirvation reisults reiacheid a scorei of 11.2 meianing that thei teiacheir's compeiteincei in compiling eind-of-seimeisteir eixam iteims was veiry good. Workshops in improving teiacheir compeiteincei in compiling eind-of-seimeisteir eixam queistions at SD Neigeiri 11 Keindari can bei carrieid out through obseirvation and monitoring by thei school principal. From thei reisults of thei analysis, thei reisults show that workshops arei veiry eiffeictivei for increiasing teiacheir compeiteincei in compiling eind-of-seimeisteir eixam queistions, beicausei teiacheirs havei thei opportunity to discuss togeitheir to study and solvei probleims baseid on conditions in thei fieild, thein theiy can correict theim or carry out follow-up in thei cyclei. neixt continuously if thei probleim has not beiein reisolveid.